2009
DOI: 10.1016/j.neuroscience.2009.04.059
|View full text |Cite
|
Sign up to set email alerts
|

Molecular interactions of the plasma membrane calcium ATPase 2 at pre- and post-synaptic sites in rat cerebellum

Abstract: SUMMARYThe plasma membrane calcium extrusion mechanism, PMCA (plasma membrane calcium ATPase) isoform 2 is richly expressed in the brain and particularly the cerebellum. Whilst PMCA2 is known to interact with a variety of proteins to participate in important signalling events (Strehler et al, 2007), its molecular interactions in brain synapse tissue are not well understood. An initial proteomics screen and a biochemical fractionation approach identified PMCA2 and potential partners at both pre-and post-synapti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 55 publications
2
34
0
1
Order By: Relevance
“…First, ATP-dependent Ca 2þ pumps, such as the plasmalemmal Ca 2þ ATPase (PMCA), move Ca 2þ across the cell membrane from the cytosol into the extracellular space. PMCA isoforms have been found both in the postsynaptic density and localized to spines, placing them appropriately to rapidly clear Ca 2þ from the spine head (Garside et al 2009;Burette et al 2010;Kenyon et al 2010). The high expression of PMCA in pyramidal neurons may explain the rapid Ca 2þ clearance capacity of these cells (Jensen et al 2004;Kip et al 2006).…”
Section: Ca 2þ Extrusionmentioning
confidence: 99%
“…First, ATP-dependent Ca 2þ pumps, such as the plasmalemmal Ca 2þ ATPase (PMCA), move Ca 2þ across the cell membrane from the cytosol into the extracellular space. PMCA isoforms have been found both in the postsynaptic density and localized to spines, placing them appropriately to rapidly clear Ca 2þ from the spine head (Garside et al 2009;Burette et al 2010;Kenyon et al 2010). The high expression of PMCA in pyramidal neurons may explain the rapid Ca 2þ clearance capacity of these cells (Jensen et al 2004;Kip et al 2006).…”
Section: Ca 2þ Extrusionmentioning
confidence: 99%
“…Although the physiological consequences of the PSD-95/PMCA4b interaction remain to be determined, PSD-95 has also been reported to induce clustering of other proteins (such as potassium channels and neurotransmitter receptors) that play an important role in the regulation of synaptic signal transduction [54][55][56] , which suggests that PMCA4b participates in the regulation of calcium signaling in the synaptic nerve terminals via PSD-95-induced clustering. In support of the function of PMCA as a regulator of calcium signaling at synapses, Garside et al [57] have analyzed PMCA interactions in synapse-enriched brain tissue from rats, and have found that PMCA2 interacts with the postsynaptic protein PSD-95, and the NMDA glutamate receptor subunits NR1 and NR2a. At the pre-synapse, PMCA2 interacts with the presynaptic protein syntaxin-1A.…”
Section: Perspectivesmentioning
confidence: 99%
“…Subsequent biochemical fractionation approaches have revealed that whilst not enriched, PMCA2 is present in the pre-synapse membrane web fraction, prepared from cerebellar cortex. Furthermore, PMCA2 makes molecular interactions within synapse-enriched protein complexes that contain syntaxin 1A, one of the components of the pre-synaptic, calciumdependent release machinery [8] . The molecular and functional Ca 2+ imaging evidence [9] also points to an important contribution from PMCA2 to pre-synaptic PF function in the cerebellum (see below).…”
Section: Pmca2 Expression At Cerebellar Synapsesmentioning
confidence: 99%
“…Further studies will be required to determine this. However, the longer C-terminus of the PMCA2b isoform seems to be functionally important in the cerebellum as its PDZ-binding sequence is capable of interacting with the synaptic PDZdomain-containing protein, PSD95 (and also PSD97), but not SAP102 [8] . This interaction, and the promiscuity of the PMCA2b PDZ sequence, was originally identified in the forebrain [12] and provided the first evidence that PMCA2b could play an important signalling role at synapses.…”
Section: Pmca2 Expression At Cerebellar Synapsesmentioning
confidence: 99%
See 1 more Smart Citation